Culture Condition for High Biomass Production of Probiotic Yeast Saccharomyces Boulardii SB2 in Shake Flask and 30 Littre Scale - Thi Luong, Dao; Van Hop, Duong; Hang, Ha Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3, 2019)
Probiotic properties in vitro of the Saccharomyces boulardii SB2 yeast, was isolated from fruit at Cuc Phuong National Park were evaluated based on biological characteristics and tolerance in simulated intestinal conditions. In the present work, studies were carried out to improve cell growth kinetics to produce cell mass of this biotherapeutic yeast in shake flaskand 30-L bioreactor levels. In case of shake flask, the highest biomass was obtained under the culture conditions as YM medium, at 37 o C, pH 6, inoculum concentration of 5 %, with shaking for 32 h; the best sources of carbon and nitrogen were found to be glucose and mixture of peptone, yeast extract, malt extract; cell dry weight and cell density reached 2.43 g L -1 and 10 9 CFU/ml repetitively. During 30-L bioreactor cultivation, the maximal cell mass in agitation speed of 200 rpm, aeration rate of 1.2 v v -1 min -1 ; at 32 h of incubation, was 3.58 g L -1 in pH controlled culture and 3.08 g L -1 in uncontrolled pH. This is considered as the first step for cell mass production of this probiotic yeast in industrial scale Keywords: Saccharomyces boulardii SB2, probiotic, biomass, shake flask, 30-L bioreactor . References [1] FAO/WHO, Guidelines for the Evaluation of Probiotics in Food, Joint FAO/WHO Working Group Report on Drafting Guidelines for the Evaluation of Probiotics in Food London, Ontario, Canada, April 30 and May 1, 2002. [2] J. Park, M.H. Floch, Prebiotics, probiotics, and dietary fiber in gastrointestinal disease, Gastroenterology Clinics of North America, 36 (2007) 47-63. https://doi.org/10.1016/j.gtc.2007. 03.001. [3] F. Mansour-Ghanaei, N. Dehbashi, K. Yazdanparast, A Shafaghi, Efficacy of Saccharomyces boulardii with antibiotics in acute amoebiasis, World Journal of Gastroenterology, 9(2003)1832-1833. https:// dx.doi.org/10.3748/ wjg.v9.i8.1832. [4] I. Castagliuolo, M.F. Riegler, L. Valenick, J.T. LaMont, C. Pothoulakis, Saccharomyces boulardii protease inhibits the effects of Clostridium difficile toxins A and B in human colonic mucosa, Infection and Immunity, 67, 1(1999)302-307. [5] A. Qamar, S. Aboudola, M. Warny, P. Michetti, C. Pothoulakis, J.T. LaMont, C.P. Kelly, Saccharomyces boulardii stimulates intestinal immunoglobulin A immune response to Clostridium difficile toxin A in mice, Infection and Immunity, 69 (2001) 2762-2765. https:// doi.org/10.1128/IAI.69.4.2762-2765.2001. [6] T.S. Chin, N.Z. Othman, R. A. Malek, N. Elmarzugi, O. M. Leng, S. Ramli, N. F. Musa, R. Aziz and H. El Enshasy, Bioprocess optimization for biomass production of probiotics yeast Saccharomyces boulardii in semi-industrial scale, Journal of Chemical and Pharmaceutical Research, 7, 3(2015)122-132. [7] D.T.N. Diep, P. George, E. Gorczyca, S. Kasapis, Studies on the viability of Saccharomyces boulardii within microcapsules in relation to the thermomechanical properties of wheyprotein. Food Hydrocolloids, 42 (2014) 232-238. https:// doi.org/10.1016/j.foodhyd.2013.07.024. [8] G.L. Miller, Use of dinitrosalicylic acid reagent for determination of reducing sugar. Analytical Chemistry, 31 (1959) 426-428 https://doi.org/ 10.1021/ac60147a030. [9] H. A. El-Enshasy and A. A. El-Shereef, Optimization of high cell density cultivation of (Probiotic/Biotherapeutic) yeast Saccharomyces boulardii adapted to dryness stress, Deutsche Lebensmittel-Rundschau 104,93(2008)89-394. [10] K. Rajkowska, A. K.-S. Bska and A. Rygala, Probiotic activity of Saccharomyces cerevisiae var.boulardii against human pathogens, Food Technology and Biotechnology, 50, 2 (2012) 230–236. [11] R. Zbinden, E.E. Gonczi, M. Altwegg, Inhibition of Saccharomyces boulardii (nom. inval.) on cell invasion of Salmonella typhimurium and Yersinia enterocolitica, Microbial Ecology in Health and Disease, 11(1999)158–162. https://doi.org/10. 1080/089106099435736. [12] D. Czerucka, T. Piche, P. Rampal, Review article: Yeasts as probiotics – Saccharomyces boulardii, Alimentary Pharmacology Therapeutics, 26(2007)767–778. https://doi.org/10.1111/j.1365 -2036.2007.03442.x. [13] L.V. Mc Farland, P. Bernacoscani, Saccharomyces boulardii. A Review of an Innovative Biotherapeutic Agent, Microbial Ecology in Health and Disease, 6(1993)157-171. https://doi. org/10.3109/08910609309141323. [14] K. Rajkowska and A. Kunicka-Styczynska, Probiotic properties of yeasts isolated from chicken feces and kefirs, Polish Journal of Microbiology, 59,4(2010) 257-263. [15] J.L.R. Fietto R.S. Araujo and F.N. Valadao, Molecular and physiological comparisons between Saccharomy cescerevisiae and Saccharomyces boulardii, Canadian Journal of Microbiology, 50 (2004) 615–621. https://doi. org/10.1139/w04-050. [16] J.L. Muller, K.L. Protti, M.S. Machado, L.L.V. Lacerda, T.M.B. Bresolin, P.S. Podlech, Comparison of Saccharomyces boulardii growth in an air-lift fermentor and in a shaker, Ciência e Tecnologia de Alimentos, 27,4(2007)688-693. http://dx.doi.org/10.1590/S0101-206120070004 00003.